Resistance and Common Ground as Functions of Mis/aligned Attitudes: A Filter-Theory Analysis of Ranchers' Writings About the Mexican Wolf Blue Range Reintroduction Project. (October 2013) - Walsh, Lynda
Writing scholars interested in stakeholder attitudes need ways to reconstruct them from archives because (a) interview/survey studies are not always feasible (particularly in historical work) and (b) the question/answer format of these studies may exclude key attitudes that emerge in unprompted expressions of opinion. Accordingly, this article argues for filter theory—a pragmatic model of interpretive attitudes—as an effective hermeneutic for archival reception studies. Complementing a previous study of administrative attitudes about the Mexican Wolf Blue Range Reintroduction Project, the present study applies filter theory to a sample of ranchers' written opinions about the Project. The main findings are as follows: Ranchers and administrators differentially value resident rights versus Project goals; ranchers warrant resistance to the Project based on these misaligned attitudes; nonetheless, both groups value the ideal of a balanced environment and evidence collected on the ground. These findings suggest the need to redefine rhetorical resistance and common ground as arguments warranted by mis/alignments between groups' interpretive attitudes. They also indicate revisions to initial recommendations for extending rhetorical common ground in the Project.